2018
DOI: 10.1038/s41523-018-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and expression profiling reveal molecular heterogeneity of disseminated tumor cells in bone marrow of early breast cancer

Abstract: Detection of disseminated tumor cells (DTCs) in bone marrow is an established negative prognostic factor. We isolated small pools of (~20) EPCAM-positive DTCs from early breast cancer patients for genomic profiling. Genome-wide copy number profiles of DTC pools (n = 45) appeared less aberrant than the corresponding primary tumors (PT, n = 16). PIK3CA mutations were detected in 26% of DTC pools (n = 53), none of them were shared with matched PTs. Expression profiling of DTC pools (n = 30) confirmed the upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 70 publications
3
20
0
Order By: Relevance
“…Abbreviation: HRS, HR-positive status. CellSearch (13-17, 25, 26) and IE/FC (18)(19)(20)(21)(22). Our previous studies in triple-negative metastatic breast cancer have demonstrated high concordance between these methods (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abbreviation: HRS, HR-positive status. CellSearch (13-17, 25, 26) and IE/FC (18)(19)(20)(21)(22). Our previous studies in triple-negative metastatic breast cancer have demonstrated high concordance between these methods (20).…”
Section: Discussionmentioning
confidence: 99%
“…Blood and bone marrow samples were subjected to the IE/FC assay to enumerate CTCs and DTCs, respectively (18)(19)(20)22). Briefly, two distinct mAbs against EPCAM, one conjugated to immunomagnetic beads (MJ37) and the other conjugated to phycoerythrin (EBA-1) were added to whole blood or bone marrow.…”
Section: Ie/fc Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Expression and functionality of the mTOR pathway were found to be associated with the proliferative switch of BMRC cells. Multiple oncogenic mutations are known to characterize benign breast cancers that do not metastasize [30,50]. Conversely, the activation of some oncogenic pathways repress BC metastasis, but increase tumor cell proliferation [3,50].…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, the presence of BRAFV600E mutation was inconsistent between PT and LN-derived DCCs [28]. Discordance between DCCs and matched PT has also been reported for the expression of estrogen receptor as well as the presence of PI3K mutations in breast cancer [30][31][32]. With regard to HER2 expression, discordance between PT has been observed for both DCCs and CTCs in non-metastatic breast cancer patients [33][34][35] indicating that adjuvant therapies could be improved by implementation of routine CTC/DCC-based stratification.…”
Section: Molecular Characterization Of Metastasis Founder Cellsmentioning
confidence: 94%